2015
DOI: 10.1016/j.paid.2014.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Applying a dual process model of self-regulation: The association between executive working memory capacity, negative urgency, and negative mood induction on pre-potent response inhibition

Abstract: This study tested a dual-process model of self-control where the combination of high impulsivity (negative urgency – NU), weak reflective / control processes (low executive working memory capacity - E-WMC), and a cognitive load is associated with increased failures to inhibit pre-potent responses on a cued go/no-go task. Using a within-subjects design, a cognitive load with and without negative emotional load was implemented to consider situational factors. Results suggested that: (1) high NU was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…According to recent study, it has been displayed that interaction between working memory capacity and social deviation forecasts alcohol involvement for three years. Results from this study are consistent with the related works (Finn & Hall, 2004;Ellingson et al, 2014;Finn, 2015), indicated that working memory capacity enables to moderate the relationship between some ass.ccsenet.org Asian Social Science Vol. 12, No.…”
Section: Discussionsupporting
confidence: 92%
“…According to recent study, it has been displayed that interaction between working memory capacity and social deviation forecasts alcohol involvement for three years. Results from this study are consistent with the related works (Finn & Hall, 2004;Ellingson et al, 2014;Finn, 2015), indicated that working memory capacity enables to moderate the relationship between some ass.ccsenet.org Asian Social Science Vol. 12, No.…”
Section: Discussionsupporting
confidence: 92%
“…Recent, highly powered factorial analyses confirm this distinction and separate a conscientiousness/planning impulsivity component from inadequate coping of negative emotionality ( Knezevic-Budisin, Pedden, White, Miller, & Hoaken, 2015 ; Sharma, Markon, & Clark, 2014 ). This view is also consistent with the proposal that poor executive and decision-making functioning is further qualified in accordance with the stronger or weaker involvement of abnormal emotion processing ( Billieux, Gay, Rochat, & Van der Linden, 2010 ; Chester et al., 2016 ; Gunn & Finn, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…Performance on tests of executive function or self-control decline with exposure to stress (Pabst, Schoofs, Pawlikowski, Brand, & Wolf, 2013; Tryon, Carter, Decant, & Laugero, 2013), increased cognitive demands (Gathmann, Pawlikowski, Scholer, & Brand, 2014; Gunn & Finn, 2015; Hinson, Jameson, & Whitney, 2003; Starcke, Pawlikowski, Wolf, Altstotter-Gleich, & Brand, 2011), and insufficient sleep (Reynolds & Schiffbauer, 2004; Rossa, Smith, Allan, & Sullivan, 2014; Whitney & Hinson, 2010). Even more troubling are studies suggesting that executive functions often fail when they are needed most, such as during “hot” states characterized by visceral arousal (Ariely & Loewenstein, 2006; Loewenstein, 1996; Metcalfe & Mischel, 1999) or with mere exposure to a tempting stimulus (Hagger et al, 2013; Heatherton & Wagner, 2011).…”
Section: The Role Of Executive Functions In Temptation Managementmentioning
confidence: 99%